2016
DOI: 10.1117/12.2225216
|View full text |Cite
|
Sign up to set email alerts
|

Noncontact blood perfusion mapping in clinical applications

Abstract: Non-contact imaging photoplethysmography (iPPG) to detect pulsatile blood microcirculation in tissue has been selected as a successor to low spatial resolution and slow scanning blood perfusion techniques currently employed by clinicians. The proposed iPPG system employs a novel illumination source constructed of multiple high power LEDs with narrow spectral emission, which are temporally modulated and synchronised with a high performance sCMOS sensor. To ensure spectrum stability and prevent thermal wavelengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…The individual pixels within the ROI could potentially preserve this notch, but the relevant phase and amplitude differences in the individual PPG signals across those pixels made the averaged signal appear “smoothed”, effectively masking the notch. The size of the kernel used to average pixels within the ROI directly influenced the iPPG signal morphology, which was confirmed by the observation made earlier in [ 4 ].…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The individual pixels within the ROI could potentially preserve this notch, but the relevant phase and amplitude differences in the individual PPG signals across those pixels made the averaged signal appear “smoothed”, effectively masking the notch. The size of the kernel used to average pixels within the ROI directly influenced the iPPG signal morphology, which was confirmed by the observation made earlier in [ 4 ].…”
Section: Resultssupporting
confidence: 80%
“…A camera-based method, also known as imaging (iPPG) or remote (rPPG) photoplethysmography, has been used to demonstrate the possibility of remote pulse rate extraction, where tissue surface is illuminated by ambient [ 2 ] or artificial light [ 3 ], and modulated backscattered light is captured by an image sensor, e.g., a digital camera. The significant downside of iPPG, compared to the traditional contact PPG, is the need of a powerful light source to spotlight the region of interest (ROI) [ 4 ]. The quality of an iPPG signal is also susceptible to the directionality and uniformity of such illumination [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to create a stabilized light flux, an illuminator comprised of individual high-power LEDs was constructed based on the principles and results reported in previous work [36]. In short, three high-power light emitting diodes (LEDs) (LXML Series, Philips, Andover, MA, USA) emitting at 530 nm with a typical half-power bandwidth of 20 nm were mounted on an aluminum substrate of high thermal conductivity to divert excess heat generated by the semiconductors (see Figure 4a).…”
Section: Methodsmentioning
confidence: 99%
“…For example, highpower quartz-halogen illumination is used for the multispectral 96 and for the long-range 74 , 75 setups, 3kw in the former and 2kW in the latter case. Iakovlev et al introduced a custom light source based on narrow-band-width high power LEDs for PPGI applications 97 . Moreover, Moco et al demonstrated that homogenous and orthogonal illumination can reduce ballistocardiographic artifacts in PPGI measurements 26 , while Trumpp et al found a significant improvement when in addition perpendicular polarization is used 98 .…”
Section: Survey Taxonomymentioning
confidence: 99%